Connecting the Qur'anic verses with reality in Ibn Ashour 's Tafsir The Concept of the (Sociality and Economy as a Model) - Al-Kilani, Kholoud; Alzyout, Abdallah (Dirasat: Human and Social Sciences, 2021)
The current study deals with the revelation of Qur'anic verses on the reality according to the concept of the sociality and economy according to Ibn Ashour through the interpretation of verification ( Tafsir al-Tahrir wa'l Tanwir). The study aims to show the concept of the revelation of Qur'anic verses on the reality as well as its benefits and types. It also aims to highlight Ibn Ashour's revelation of Qur'anic verses on the reality in both ways sociality and economy. I had accomplished to several results, the most prominent care Ibn Ashour in the modern reality and his care of the social and economic situation that he has experienced.